2019
DOI: 10.1016/j.scriptamat.2019.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation behaviour and mechanical properties of a novel Al0.5MoTaTi complex concentrated alloy

Abstract: The precipitation behaviour in a novel Al0.5MoTaTi complex concentrated alloy (CCA) is described in this study. The alloy was fabricated through an arc-melting process. Solution heat treatment and additional aging was performed at 1673 K and 1273 K. It was found, that a disordered body-centred cubic phase (bcc) precipitates in cuboidaland loop-shaped form within an ordered B2 phase. The mechanism of the formation of the loops is believed to be related to the transformation of anti-phase boundaries (APB) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
(35 reference statements)
2
8
0
Order By: Relevance
“…The pattern of the powders milled for 12 h is also presented for comparison. The theoretical crystal lattice parameter a mix of the bcc solid solution in non-equiatomic (W35Ta35Mo15Nb15)95Ni5 RHEA is calculated to be a mix = 0.324 nm using the rule of mixtures, while the lattice parameter of as-sintered bulk RHEA determined by the XRD is 0.320 nm based on Nelson-Riley approach [17]. It can be concluded that the calculated value for the (W35Ta35Mo15Nb15)95Ni5 RHEA is very close to the experimental result.…”
Section: Phase and Microstructure Of The Bulk Rheasupporting
confidence: 61%
See 2 more Smart Citations
“…The pattern of the powders milled for 12 h is also presented for comparison. The theoretical crystal lattice parameter a mix of the bcc solid solution in non-equiatomic (W35Ta35Mo15Nb15)95Ni5 RHEA is calculated to be a mix = 0.324 nm using the rule of mixtures, while the lattice parameter of as-sintered bulk RHEA determined by the XRD is 0.320 nm based on Nelson-Riley approach [17]. It can be concluded that the calculated value for the (W35Ta35Mo15Nb15)95Ni5 RHEA is very close to the experimental result.…”
Section: Phase and Microstructure Of The Bulk Rheasupporting
confidence: 61%
“…where ε, D and b are lattice strain, grain size and Burgers vector, respectively. b is equal to √ 3 2 a (a is the lattice parameter determined in the means of the Nelson-Riley approach with the weighting function 1/2(cot 2 θ + cos θ cot θ) [17]) for a bcc structure, ε and D are calculated from the XRD patterns based on Equation (2).…”
Section: Alloying Processmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The additional phases formation can be expected since Ti and Nb are known to be bcc phase stabilizers in RHEAs [2,43], while Al is a compound former, at least in certain combinations of elements [43][44][45]. However, no experimental information on the effect of Ni on the structure and properties of RHEAs was available before.…”
Section: Phase Composition and Microstructure Of The Ti-nb-cr-v-ni-al Alloysmentioning
confidence: 99%
“…However, most of bcc/B2 RHEAs are brittle since the B2 phase is a continuous matrix with bcc precipitates [12,13]. Only some RHEAs can have a ductile bcc matrix with embedded B2 strengthening particles after proper treatment [14,15].…”
Section: Introductionmentioning
confidence: 99%